Read count-based method for high-throughput allelic genotyping of transposable elements and structural variants - Kuhn, Alexandre (BMC Genomics, 2015)
BACKGROUND: Like other structural variants, transposable element insertions can be highly polymorphic across individuals. Their functional impact, however, remains poorly understood. Current genome-wide approaches for genotyping insertion-site polymorphisms based on targeted or whole-genome sequencing remain very expensive and can lack accuracy, hence new large-scale genotyping methods are needed. RESULTS: We describe a high-throughput method for genotyping transposable element insertions and other types of structural variants that can be assayed by breakpoint PCR. The method relies on next-generation sequencing of multiplex, site-specific PCR amplification products and read count-based genotype calls. We show that this method is flexible, efficient (it does not require rounds of optimization), cost-effective and highly accurate. CONCLUSIONS: This method can benefit a wide range of applications from the routine genotyping of animal and plant populations to the functional study of structural variants in humans. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1700-4) contains supplementary material, which is available to authorized users.